2019
DOI: 10.1039/c9qo00155g
|View full text |Cite
|
Sign up to set email alerts
|

Chiral self-sorting behaviour of [2.2]paracyclophane-based bis(pyridine) ligands

Abstract: [2.2]Paracyclophane-based bis(pyridine) ligands form dinuclear complexes upon coordination to palladium(ii) ions, however, with distinct differences concerning their chiral self-sorting ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…[2][3] In recent years synthetic methodologies to functionalise the pCp core have been developed and a variety of functional groups have been precisely positioned on the rings and bridges of pCp. [4][5] For example, Spuling, Sharma and co-workers 6 have recently reported the first examples of pCp compounds emitting via a thermally activated delayed fluorescence mechanism 7 due to the presence of a diphenylamine donor and a benzophenone acceptor units located on different decks of the pCp. Zafra and co-workers 8 reported a pCp skeleton functionalized with stilbenoid compounds possessing terminal donor-donor, acceptor-acceptor or donor-acceptor units that have the ability to promote charge and exciton migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3] In recent years synthetic methodologies to functionalise the pCp core have been developed and a variety of functional groups have been precisely positioned on the rings and bridges of pCp. [4][5] For example, Spuling, Sharma and co-workers 6 have recently reported the first examples of pCp compounds emitting via a thermally activated delayed fluorescence mechanism 7 due to the presence of a diphenylamine donor and a benzophenone acceptor units located on different decks of the pCp. Zafra and co-workers 8 reported a pCp skeleton functionalized with stilbenoid compounds possessing terminal donor-donor, acceptor-acceptor or donor-acceptor units that have the ability to promote charge and exciton migration.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are only three examples of pCp scaffolds used in metallosupramolecular self-assembly. 5,[17][18] The first is a small PdL2 macrocyclic structure where L represents pCp compounds functionalized with two ethynyl-2-pyridyl groups, 17 the second example reported by Lützen and co-workers, 5 with Pd 2+ produces multiple products, the structures of which could not be identified by ESImass spectrometry. As a result of the six photoactive pCp molecules rigidly assembled in the 3D cage-like structure, pCpd4py-Pd is emissive in both dichloromethane solution, lPL= 455 nm, and as a powder, lPL= 450 nm, with FPL of 5% and 3%, respectively in solution and the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…The two benzene rings of the [2.2]paracyclophane (pCp) are disposed cofacially (Bahrin et al, 2017, 2), which give rise to through-space (π-π trans-annular) and through-bond [σ(bridge)-π(annular)] electronic interactions, affecting the chemical, optical, and electronic properties of the molecule (Kahnt et al, 2007;Elacqua and MacGillivray, 2010). It has been shown that positioning organic functional groups on the pCp core ring shifts its luminescence properties (Braun et al, 2017;Anhäuser et al, 2019;Rota Martir et al, 2019). Exploiting the electronic coupling present between the two benzene decks of the pCP, the first examples of pCp compounds emitting via a thermally activated delayed fluorescence mechanism were recently reported by Spuling, Sharma and coworkers (Spuling et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[22] Mastering the self-sorting behavior is of utmost importance to cope with the immense structural complexity that such systems offer. [23][24][25][26][27] Thus the exploration and understanding of the factors that affect the structural self-assembly is essential for crystal engineers who design structures, in particular those of materials based on coordination networks with racemic ligands. recognition or self-discrimination of the ligand units.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rudbari group has reported that the reaction of a racemic mixture of Schiff base tridentate ligand with vanadium(V) affords homochiral vanadium complex in a ligand self‐recognition process, and the Bian group reported that a racemic bisbipyridines ligand discriminates its own chirality and results in a heterochiral metallocycle in a chiral self‐discriminating manner . Mastering the self‐sorting behavior is of utmost importance to cope with the immense structural complexity that such systems offer . Thus the exploration and understanding of the factors that affect the structural self‐assembly is essential for crystal engineers who design structures, in particular those of materials based on coordination networks with racemic ligands.…”
Section: Introductionmentioning
confidence: 99%